Spatial voting in non-partisan cities: A case study. (April 2023) - Lucas, Jack; McGregor, R. Michael; Bridgman, Aengus
Abstract: In spatial voting theory, voters choose the candidate whose policy preferences are most like their own. This requires that (a) voters and candidates have policy preferences that can be meaningfully summarized in terms of low-dimensional "ideal points" on a left-right scale; (b) voters are able to discern, either directly or through relevant cues, the ideal points of the candidates who are running for office; and (c) voters incorporate this information into the choices they make at the ballot box. Perhaps more than in any other elections, it is not clear that any of these requirements are met in non-partisan municipal elections: policy preferences may not be ideologically structured, information may be inadequate, and voters may choose candidates for reasons other than ideology. This makes non-partisan municipal elections an especially hard test for spatial voting theory. Using novel data from both municipal candidates and eligible voters in a major non-partisan municipal election in Canada, we show that municipal policy attitudes are ideologically structured and that these municipal policy ideal points are strongly related to mayoral and council vote choice. Thus, despite the institutional and informational obstacles, spatial voting can play an important role in non-partisan municipal elections.